A CONTRASTIVE STUDY OF SYMBOLIC MEANINGS OF “DOG” IN CHINESE AND VIETNAMESE IDIOMS FROM A COGNITIVE PERSPECTIVE (Journal of Foreign Language Studies, 2024)
Dog plays a significant role in the lives of Vietnamese and Chinese people. The implications and images of ‘dog’ in idioms are commonly expressed in both languages. However, due to the discrepancies in social contexts, perceptions, and customs of the two countries, the conceptual and metaphorical meanings as well as the interpretation of ‘dog’ in Chinese and Vietnamese idioms are different. Although this reflects the unique cultural features of each language, Vietnamese learners are often interfered by their first language when learning Chinese idioms containing ‘dog’. This contrastive study analyzes the symbolic meanings of ‘dog’ in Chinese and Vietnamese idioms. The findings reveal that ‘dog’ has 02 similar symbolic meanings in both Chinese and Vietnamese, 08 distinctive meaning merely found in the former and 05 merely in the latter, posing difficulties for Vietnamese learners in the acquisition of Chinese idioms containing ‘dog’. This study is expected to help learners rectify language interference errors for better understanding and usage of Chinese idioms.
Keywords: Chinese; Vietnamese; idiom; 狗（犬）/ dog; symbolic meaning; cognition